Characterization of Δ7/11, a functional prolactin-binding protein - Fleming, JM (2012)
Prolactin is essential for normal mammary gland development and differentiation, and has been shown to promote tumor cell proliferation and chemotherapeutic resistance. Soluble isoforms of the prolactin receptor have been reported to regulate prolactin bioavailability by functioning as “prolactin binding proteins.” Included in this category is Δ7/11, a product of alternate splicing of the prolactin receptor primary transcript. However, the direct interactions of prolactin withΔ7/11, and the resulting effect on cell behavior, have not been investigated. Herein, we demonstrate the ability of Δ7/11 to bind prolactin using a novel proximity ligation assay and traditional immunoprecipitation techniques. Biochemical analyses demonstrated that Δ7/11 was heavily glycosylated, similar to the extracellular domain of the primary prolactin receptor, and that glycosylation regulated the cellular localization and secretion of Δ7/11. Low levels of Δ7/11 were detected in serum samples of healthy volunteers, but were undetectable in human milk samples. Expression of Δ7/11 was also detected in six of the 62 primary breast tumor biopsies analyzed; however, no correlation was found with Δ7/11 expression and tumor histotype or other patient demographics. Functional analysis demonstrated the ability of Δ7/11 to inhibit prolactin-induced cell proliferation as well as alter prolactin-induced rescue of cell cycle arrest/early senescence events in breast epithelial cells. Collectively, these data demonstrate that Δ7/11 is a novel regulatory mechanism of prolactin bioavailability and signaling.